Hodgkin's lymphoma as a rare variant of Richter's transformation in chronic lymphocytic leukemia: A case report and review of the literature - JANJETOVIC, SNJEZANA (Mol Clin Oncol, 2016)
Richter's transformation induces an aggressive clinical course in chronic lymphocytic leukemia (CLL). In the majority of cases, Richter's transformation manifests itself as a high-grade B-cell non-Hodgkin's lymphoma (B-NHL). However, other histological types, such as classical Hodgkin lymphoma (cHL), lymphoblastic lymphoma, hairy cell leukemia and high-grade T-cell NHL have been described previously. The present study reports a rare case of CLL with transformation into classical Hodgkin's lymphoma (cHL). The common clonal origin of CLL and cHL was documented by immunoglobulin gene rearrangement analysis performed using multiplex polymerase chain reaction. Following a review of the literature, treatment of secondary Hodgkin's lymphoma is discussed, and prognosis is often poor.